Biofilm Production and Antimicrobial Resistance among Uropathogens in Pediatric Cases: a Hospital Based Study - Shrestha, Dhiraj; Thapa, Pratigya; Bhandari, Dinesh; Parajuli, Hiramani; Chaudhary, Prakash; Thapa, Kabi; Sharma, Vijay Kumar; Shah, Pradeep Kumar (Journal of Nepal Health Research Council, 2018)
Background: The study was designed to provide account of etiological agents of urinary tract infection in pediatric patients and the antimicrobial resistance pattern plus biofilm producing profile of the isolates. Methods: The prospective study was conducted in Alka Hospital, Nepal with 353 clean catch urine samples from children. It was obtained during July 2014 to January 2015 which were first cultured by semi-quantitative method, followed by antimicrobial susceptibility testing and biofilm production assay on Congo red agar. Multidrug- resistance, extensively drug- resistance and pandrug- resistance among isolates were considered as per international consensus. Results: Out of 353 samples, 64 (18.13%) showed positive growth in culture, confirming urinary tract infection. E. coli, 44 (68.8%) was the predominant organism followed by Klebsiella spp. 6 (14.1%). Most E. coli were sensitive to amikacin (93.2%) followed by nitrofurantoin (86.4%), and highly resistant to ampicillin (95.5%). Of 64 isolates, 23 (35.93%) were found to be multidrug- resistant strains. Biofilm was produced by 36 (56.25%) isolates. Conclusions: This study showed higher biofilm production and resistance to in-use antibiotics rendering ineffective for empirical use. Regular surveillance of resistance patterns should be done to regulate multidrug- resistant bugs and to ensure effective management of urinary tract infection in children in a tertiary care setups.